Risk Leadership and Emotional Intelligence on ISO 31000 Application’s Effectiveness for Organisation - Ardilo, Aldi (Interdisciplinary Social Studies, 2022)
Background: ISO 31000 indicates that risk management is a science in which competencies are embedded in the individuals. It also emphasises the importance of having proper leadership while demonstrating the commitment towards risk management implementation. Humans are emotional creatures—we could sometimes be influenced by the force of feelings, rather than rational discussion. Aim: This paper describes the dynamics of emotional intelligence and risk leadership in implementing risk management. Method: The research used a qualitative descriptive design with the verification strategy of the case study. It used a non-probability sampling to individuals in the top management position. Findings: The findings suggest that without a proper level of emotional intelligence, it is difficult for leaders to cultivate an effective risk culture. These findings may equip decision-makers on the interrelationships between emotional intelligence, risk culture, and an organisation’s risk management maturity.